2020
DOI: 10.1007/s10842-019-00325-0
|View full text |Cite
|
Sign up to set email alerts
|

The Failure of French Industrial Policy

Abstract: France, for a century, thought of herself as a great industrial nation. This country not only saw a source of prosperity and quality jobs for its citizens but also always considered technological autonomy and industrial power as an attribute of sovereignty. For the classical economist, deindustrialization is a fact of development: the more economies grow and become more sophisticated, the more they produce and consume services, and the more industrial activities migrate to emerging countries. However, in Franc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Compared to its neighbours, France has seen its manufacturing base shrink dramatically since the 1980s (Minovez 2019 ; Buigues and Cohen 2020 ). In 2019, it represented only 10% of GDP, against 30% at the end of the 1970s and 15% in 2008.…”
Section: Industrial Policy Renewal In France Since 2008mentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to its neighbours, France has seen its manufacturing base shrink dramatically since the 1980s (Minovez 2019 ; Buigues and Cohen 2020 ). In 2019, it represented only 10% of GDP, against 30% at the end of the 1970s and 15% in 2008.…”
Section: Industrial Policy Renewal In France Since 2008mentioning
confidence: 99%
“…This questioning is highly relevant in France, where a renewal of industrial policy and recurrent changes in the policymaking process have been observed since 2008 (Klebaner and Assogba 2018 ; Buigues and Cohen 2020 ; Voy-Gillis and Lluansi 2020 ). As in the UK, France’s manufacturing base has been shrinking since the 1980s (Minovez 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…In Germany, the fall in industrial employment has been slower than in Britain, but has more than halved since the 1970s (Tomlinson, 2017). In France, there has been a similar decline in the GDP share of the manufacturing industry (Buigues and Cohen, 2020). Throughout Europe, workers have moreover endured a major fall in the real value of their wages over the last decades (Hopkin, 2017: 470).…”
Section: The Enemy Within: Policing the (Migrant) Crisismentioning
confidence: 99%